2019
DOI: 10.3389/fphar.2019.00962
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Clinicopathological Significance of PD-L1 in Patients With Bladder Cancer: A Meta-Analysis

Abstract: Background: The prognostic role of programmed cell death-ligand 1 (PD-L1) in bladder cancer has been investigated in previous studies, but the results remain inconclusive. Therefore, we carried out a meta-analysis to evaluate the prognostic significance of PD-L1 in patients with bladder cancer. Methods: The electronic databases PubMed, Embase, Web of Science, and Cochrane Library were searched. The association between PD-L1 expression and survival outcomes and clinicopathological factors was analyzed by hazard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 42 publications
(112 reference statements)
1
28
1
Order By: Relevance
“…The prognostic value of PD-L1 was also investigated in previous studies using a meta-analytic approach. A meta-analysis including 11 studies demonstrated that PD-L1 overexpression was a predictor of worse survival outcomes in bladder cancer (29). Furthermore, high PD-L1 was significantly correlated with later tumor stages (OR = 3.9, 95%CI = 2.71.5.61, p < 0.001) and distant metastases (OR = 2.5, 95%CI = 1.22.5.1, p = 0.012) in bladder cancer (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognostic value of PD-L1 was also investigated in previous studies using a meta-analytic approach. A meta-analysis including 11 studies demonstrated that PD-L1 overexpression was a predictor of worse survival outcomes in bladder cancer (29). Furthermore, high PD-L1 was significantly correlated with later tumor stages (OR = 3.9, 95%CI = 2.71.5.61, p < 0.001) and distant metastases (OR = 2.5, 95%CI = 1.22.5.1, p = 0.012) in bladder cancer (29).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis including 11 studies demonstrated that PD-L1 overexpression was a predictor of worse survival outcomes in bladder cancer (29). Furthermore, high PD-L1 was significantly correlated with later tumor stages (OR = 3.9, 95%CI = 2.71.5.61, p < 0.001) and distant metastases (OR = 2.5, 95%CI = 1.22.5.1, p = 0.012) in bladder cancer (29). Another meta-analysis on non-small cell lung cancer (NSCLC) showed that PD-L1 expression was significantly associated with histology type, differentiation, and tumor stage, whereas the relationship between PD-L1 expression and OS was not statistically significant (p = 0.863) (30).…”
Section: Discussionmentioning
confidence: 99%
“…But, PD-L1 expression on clinical prognosis is poorly defined in UC. Some studies have suggested that PD-L1 overexpression was correlated with poor prognosis in bladder cancer (25)(26)(27). On the other hand, some studies reported that PD-L1 expression has no correlation with clinical outcome in UC (28,29).…”
mentioning
confidence: 99%
“…As an immunosuppressive molecule, PD-L1 can inhibit the activity of T cells through a variety of complex signaling pathways, thus promoting tumor progression [ 17 19 ]. The relationship between the expression of PD-L1 and the prognosis of different cancer patients has been controversial.…”
Section: Discussionmentioning
confidence: 99%